اصول فقہ کی تدوین میں سائنسی اساسیات و ضرورت واہمیت: Scientific fundamentals in the compilation of Usool-Ul-Fiqh Need and Significance - Muhammad Junaid Anwar (jihat-ul-islam, 2021)
There are foundations for the solution of the new problems that arise in the religious sciences every day, and the solution of these problems is also offered by the scholars and intellectuals and in this case as much as possible new research and theories are used. It has been observed that in some places there are things which are still based on the philosophical terms of the ancient times and the terms which the pioneers have mentioned in their books have been continued by the later ones.Otherwise, there should have been an attempt to compile the Usoo;-ul-Fiqh in unspecified issues (especially in issues related to medical sciences) according to modern scientific research or on scientific grounds. It can make easier to deduce the solution to the modern problems that would have arisen. This should lead to a new foundation of Usool-ul-Fiqh emerged in the changing rulings and it would certainly lead to a better solution. In the modern era, the various spheres of human life and the social sciences have come together in such a way that by refining and scrutinizing them, they can refine the real situation and make it easier for the people in a scientific way based on modern scientific and proven principles. It has become very important to put it into practice.This work requires competitive persons at the individual and collective level who try to clarify any issue in the light of various sciences from various aspects of it. It takes time to consider new foundations. specially when it is a matter of laying the groundwork for changes in the Usool-ulFiqh based on scientific principles.It should be noted that in understanding the real jurisprudence, the experts will be consulted, but the ruling will be applied only by a group of scholars and jurists, because in modern issues, the differences and diversity of circumstances are very complex. Problems are so intertwined with other sciences that until a satisfactory knowledge of the aspects related to them is acquired, it will not be possible to gain power over its correct shar'i position and ruling. It is necessary to rethink the use of known scientific research instead of the old philosophical terms in this age and where necessary to use them as the basis of the principles of jurisprudence.